SPATIAL AND TEMPORAL ANALYSIS OF COVID-19 CASES DISTRIBUTION IN SUKOHARJO REGENCY: Analisis Spasial dan Temporal Distribusi Kasus COVID-19 di Kabupaten Sukoharjo - Wulan Istri Hastari; Diaz Amel Lolita; Lukman Fauzi (Universitas Airlangga, 2023)
Background: COVID-19 has become a public health challenge in Sukoharjo Regency, as its cumulative cases reached 15,258 confirmed cases with 1,380 deaths (CFR 9.04%). Spatial and temporal analysis can provide an overview of the spatial and temporal factors associated with the disease and explain the analysis of the disease distribution in a population to clarify the transmission mechanism. Purpose: This study aimed to provide an overview of the spatial and temporal distribution of COVID-19 cases in the Sukoharjo Regency and determine the spatial autocorrelation of the distribution of COVID-19 cases in the Sukoharjo Regency. Methods: This was an observational study with an ecological design. The data used was Secondary data collected from the Health Office of Sukoharjo, with the population of all COVID-19 confirmed cases recorded by the Health Office of Sukoharjo from 2020 to 2021. The sample was 15,528 patients. Results: The highest number of COVID-19 cases in Sukoharjo Regency was found in the Baki Sub-district (242.23/10,000 people). In comparison, the lowest number of cases was found in the Polokarto Sub-district (114.60/10,000 people). The Sukoharjo Regency experienced two waves of COVID-19, and its peak occurred in July 2021. The results showed spatial dependence in the COVID-19 case distribution with a Moran'sI value of 0.36, z-score of 7.50, and p-value <0.01. Conclusion: The highest number of COVID-19 findings occurred in July 2021, and there was spatial autocorrelation in the distribution of COVID-19 cases in the Sukoharjo Regency with a clustered transmission pattern.